Compound Heterozygous Hemoglobin SD Disease Presenting as Sickle Cell Crisis in Pregnancy - Rakhi; Rohilla Minakshi; Malhotra Pankaj; Das Reena; Jain Vanita; Prasad GRV; Kalra Jasvinder (Journal of Women's Reproductive Health, 2016)
A case report of compound heterozygous hemoglobin SD disease presenting as sickle crisis during pregnancy. The discussion covers transfusion, pain control, and peripartum care.